2016
DOI: 10.1155/2016/8543561
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect ofAmphipterygium adstringensExtract on Dextran Sulphate Sodium-Induced Ulcerative Colitis in Mice

Abstract: Amphipterygium adstringens is an endemic species in Mexico commonly known as “cuachalalate.” Healers to treat gastritis, gastric ulcers, and gastrointestinal cancer have traditionally used the bark. We investigated the effects of alcoholic extract of A. adstringens (AaEE) in DSS-induced colitis in mice. The protective effect of AaEE was determined at 200 mg/kg by oral gavage for 10 days. We determine the effect of AaEE on clinical features (disease activity index), antioxidants, anti-inflammatory, and immunomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 47 publications
3
20
1
1
Order By: Relevance
“…Because A. adstringens and C. procera are members of the same family, Anacardiaceae, and due to their commercial presentation, these, like many other plants sold in markets, are liable to adulteration [14]. In this work, we demonstrated that the biomedical and therapeutic properties that the C. procera methanolic extract exerted in this DSS-induced colitis model are very similar to those of A. adstringens, which was studied previously by our work team [4]. Both C. procera and A. adstringens extracts had remarkable antioxidant and anti-inflammatory effects and greatly diminished UC severity.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Because A. adstringens and C. procera are members of the same family, Anacardiaceae, and due to their commercial presentation, these, like many other plants sold in markets, are liable to adulteration [14]. In this work, we demonstrated that the biomedical and therapeutic properties that the C. procera methanolic extract exerted in this DSS-induced colitis model are very similar to those of A. adstringens, which was studied previously by our work team [4]. Both C. procera and A. adstringens extracts had remarkable antioxidant and anti-inflammatory effects and greatly diminished UC severity.…”
Section: Discussionsupporting
confidence: 71%
“…The electrondonating capacity of the extract was calculated from the bleaching of the purple-colored DPPH solution dissolved in methanol. Ninety-six-well ELISA plates were filled with extract concentrations ranging from 1 to 100 μg/mL and 100 μM DPPH solution [4]. Quercetin was used as a control, and the same concentrations of the extract were used.…”
Section: Lipid Peroxidationmentioning
confidence: 99%
See 2 more Smart Citations
“…Inflammation responses are one of the most crucial factors causing UC [ 3 ]. The increased pro-inflammatory cytokines such as TNF-α, IFN-γ, and IL-1β, extend the inflammatory cascade and eventually lead to intestinal/colonic tissue damage in UC induced by DSS [ 4 ].…”
Section: Introductionmentioning
confidence: 99%